Political Transition of the Military Regime in Latinamerica - Aigneren, Miguel (La Sociología en sus Escenarios, 2009)
Abstract. This paper attempts an analysis of the Chilean political society from the perspective of the problem of transition from a authoritarian regime to civilian regime. It begins with some general reflections on the political transition of the authoritarian regime in Latin America. Also, analyze the role of political organizations under civilian regimes, distinguishing among various regime phases and types of organizations and mobilizations, and goes on to outline changing state/societal relations in Chile. The paper presents some interpretative details about the paradoxical role of social crisis of civil society and their political organizations and mobilizations, their fundamental importance in reconstituting civil society and transforming authoritarian regimes, and their limits with respect to bringing about the restoration of full and real democracy. This paper is several things: a record of an important historical process, a compendium of information and analysis about the political transition of the military regime, a source book of political debates conveniently tied to a concrete case, on the nature and strategy of the transition to democracy. And, one of the three “tracks paper” system: A draft theoretical paper for the Ph. D. degree qualifying examination. Resumen. Este trabajo intenta un análisis de la sociedad política chilena desde la perspectiva del problema de la transición de un régimen autoritario al régimen civil. Se comienza con algunas reflexiones generales sobre la transición política del régimen autoritario en América Latina. También, analizar el papel de las organizaciones políticas en virtud de los regímenes civiles, distinguiendo entre las diversas fases de régimen y los tipos de organizaciones y movilizaciones, y pasa a describir el cambio de estado / relaciones sociales en Chile. El artículo presenta algunos detalles acerca de la interpretación paradójica de la función de la crisis social de la sociedad civil y sus organizaciones políticas y movilizaciones, su importancia fundamental en la reconstitución de la sociedad civil y la transformación de los regímenes autoritarios, y sus límites con respecto a lograr el restablecimiento de la plena y verdadera democracia . El presente trabajo es varias cosas: un registro de un importante proceso histórico, un compendio de información y análisis acerca de la transición política del régimen militar, un libro de los debates políticos convenientemente vinculada a un caso concreto, de la naturaleza y la estrategia de la transición A la democracia. Y, uno de los tres "pistas de papel" del sistema: un proyecto de documento teórico para el doctorado grado de calificación de examen.